Effects of Early Adolescent Alcohol Use on Mid‐Adolescent School Performance and Connection: A Longitudinal Study of Students in Victoria, Australia and Washington State, United States. (November 2014) - Hemphill, Sheryl A.; Heerde, Jessica A.; Scholes‐Balog, Kirsty E.; Herrenkohl, Todd I.; Toumbourou, John W.; Catalano, Richard F.
ABSTRACT BACKGROUND This article examines the effect of early adolescent alcohol use on mid‐adolescent school suspension, truancy, commitment, and academic failure in Washington State, United States, and Victoria, Australia. Also of interest was whether associations remain after statistically controlling for other factors known to predict school outcomes. METHODS State‐representative student samples were surveyed in 2002 (grade 7; N = 1858) and followed up annually to 2004 (grade 9) in both sites. Students completed a modified version of the Communities That Care survey to report alcohol use, school outcomes, and risk and protective factors. Response rates were above 74% and retention rates exceeded 98% in both places. RESULTS Controlling for grade 7 risk factors, grade 7 current alcohol use, and heavy episodic drinking were associated with grade 8 school suspension. Grade 7 current and frequent alcohol use and heavy episodic drinking were linked to grade 9 truancy. In fully adjusted analyses, associations between early alcohol use and academic failure and low school commitment did not remain. CONCLUSIONS Although alcohol use is one factor influencing school performance and connection, there are other risk factors that need to be targeted to improve school outcomes.